If you meant to solve for x...
Answer:
There is not enough here to answer this problem
Step-by-step explanation:
Sorry : (
In order to use the elimination method, we have to multiply the equation by some number, so that one of the variable has the same coefficient.
For example, multiplying the first equation by 3 and the second by 2 gives the following, equivalent system:
![\begin{cases}6x-15y=33\\6x+4y=14\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D6x-15y%3D33%5C%5C6x%2B4y%3D14%5Cend%7Bcases%7D)
Now, we can subtract the two equations, and we will cancel (eliminate) the x variable:
![-19y=19 \iff y=-1](https://tex.z-dn.net/?f=%20-19y%3D19%20%5Ciff%20y%3D-1%20)
Now that y is known, plug it into one of the equations: for example, if we use the first one we get
![2x+5 = 11 \iff 2x = 6 \iff x=3](https://tex.z-dn.net/?f=%202x%2B5%20%3D%2011%20%5Ciff%202x%20%3D%206%20%5Ciff%20x%3D3%20)
Answer:
![x^2-12x+27 =0](https://tex.z-dn.net/?f=x%5E2-12x%2B27%20%3D0)
Step-by-step explanation:
Given a Parabola that intersects the x-axis at x=3 and x=9.
I presume you want to determine the equation of the parabola.
You can use this form:
Given roots of a parabola, the equation of the parabola is derived using the formula:
![x^2-($Sum of Roots)x+Product of Roots =0\\Since roots are 3 and 9, the equation becomes:\\x^2-(3+9)x+(3X9) =0\\x^2-12x+27 =0](https://tex.z-dn.net/?f=x%5E2-%28%24Sum%20of%20Roots%29x%2BProduct%20of%20Roots%20%3D0%5C%5CSince%20roots%20are%203%20and%209%2C%20the%20equation%20becomes%3A%5C%5Cx%5E2-%283%2B9%29x%2B%283X9%29%20%3D0%5C%5Cx%5E2-12x%2B27%20%3D0)
The equation of the parabola is:
![x^2-12x+27 =0](https://tex.z-dn.net/?f=x%5E2-12x%2B27%20%3D0)